Ethnobotany of traditional medicine in Akit Tribe, Teluk Setimbul Village, Karimun District, Indonesia - TISRIN MAULINA DEWI; WORO SUMARNI; LANGLANG HANDAYANI; MUHIRI MUHIRI (Society for Indonesian Biodiversity, 2024)
Abstract. Dewi TM, Sumarni W, Handayani L, Muhiri. 2024. Ethnobotany of traditional medicine in Akit Tribe, Teluk Setimbul Village, Karimun District, Indonesia. Biodiversitas 25: 2696-2704. The Akit Tribe has long been using indigenous knowledge of medicinal herbs for their purposes. Unfortunately, due to their wasteful lifestyle, lack of written records, and oral transmission of knowledge, the Akit Tribe's native wisdom is today in danger of disappearing. This study aims to document traditional medicinal plants used by the Akit Tribe. The research approach used is descriptive qualitative using a field survey. Informants were selected using the purposive sampling method. The informants interviewed consisted of the main resource person (customary leader), key resource person (shaman), and individuals knowledgeable in the identification and collection of medicinal plants. Data were obtained through in-depth interviews and participatory observations. Data analysis used descriptive qualitative. This study obtained 40 plants from 23 families used for traditional medicine of the Akit Tribe, were with the Zingiberaceae family as the most widely used family (5 species). The parts of the plant used by the Akit Tribe for treatment are leaves, roots, stems, fruits, flakes, rhizomes, and the whole plant with leaves being the most widely used part of the plant (19 species). The way of processing medicinal plants is also still considered simple, processing by boiling and then drinking is the most widely used. This research has significant implications for cultural preservation, biodiversity conservation, pharmacological research, socio-economic development, public health, and education. It serves as a critical step in safeguarding the traditional knowledge of the Akit Tribe while also exploring its potential contributions to wider fields.